Mendelian Randomization Rules Out Causation Between Inflammatory Bowel Disease and Non-Alcoholic Fatty Liver Disease - Chen, Lanlan; Fan, Zhongqi; Sun, Xiaodong; Qiu, Wei; Chen, Yuguo; Zhou, Jianpeng; Lv, Guoyue (Frontiers in Pharmacology, 2022)
Background: Inflammatory bowel disease (IBD) and non-alcoholic fatty liver disease (NAFLD) usually co-exist clinically. However, whether such association is causal is still unknown. Methods: Genetic variants were extracted as instrumental variables from the largest genome-wide association study (GWAS) of IBD, Crohn’s disease (CD) and ulcerative colitis (UC) with 25,042 cases and 34,915 controls (GWAS p-value < 5x10-8). Information of genetic variants in NAFLD was extracted from a GWAS with 1,483 cases and 17,781controls. Also, liver fat content (LFC) was included as the outcome. Then, a bi-direction Mendelian randomization (MR) was carried out to appraise the causal relationship between NAFLD on IBD. Besides, a multivariable MR (MVMR) design was carried to adjust for body mass index (BMI) and type 2 diabetes (T2D) as well. Results: Generally, IBD might not affect the risk of NAFLD (OR = 0.994[0.970, 1.019]), together with its subtypes including UC and CD. However, genetically-elevated risk of IBD might cause liver fat accumulation (beta = 0.019, p-value = 0.016) while turning insignificant at Bonferroni correction. Besides, no causal effect of NAFLD on IBD was observed (OR = 0.968[0.928, 1.009]), together with UC and CD. Also, genetically-elevated LFC could not impact IBD, UC and CD either. The MR CAUSE analysis supported these null associations and MVMR analysis also supported such null associations even after adjusting for BMI and T2D. Conclusion: This MR study ruled out the causal relationship between IBD and NAFLD, suggesting therapeutics targeting NAFLD might not work for IBD and vice versa.